6 - Healing Insanity: Skills and Expert Knowledge of Igbo Healers: DOI: 10.4314/ad.v30i3.22231 - Iroegbu, Patrick (Africa Development, 2005)
This paper gives insight into how Igbo healers of Southern Nigeria conceive of insanity and apply endogenous knowledge and expertise to heal it, contrary to the belief that cosmopolitan orthodox medicine only can provide efficacious cure for insanity. Resort to community support and culture remains people's widely shared way of dealing with insanity and related disturbances. While phar maceutical drugs are being made available to health seekers, local herbal and ritual resources as well as communicational and bodily skills do constitute the asset for holistic healing. Although research shows tensions between the local, Christian and biomedical views, the paper argues that effective healing tends to be successful when the etiology and treatment include due ancestral compliance work in harmony with people's views, emotions and life-worlds. The paper of fers an endogenous theory of symbolic release underlying a genuinely Igbo cosmological and epistemological strategy, side by side with the ritual of tying and untying for releasing the forces hampered by intrusion, and for achieving treatment based on culturally meaningful herbal and animal resources. To res cue the help-seeking individual and kin-group, as a first principle, the forces that tie the afflicted need to be rusticated before effective results can be obtained with treatment.